Thermal Freeze-Out Parameters and Pseudoentropy from Charged Hadron Spectra in High-Energy Collisions - Zhang, Xu-Hong; Gao, Ya-Qin; Liu, Fu-Hu; Olimov, Khusniddin K. (Advances in High Energy Physics, 2022)
We collected the transverse momentum (mass) spectra of charged hadrons (π−, π+, K−, K+, p¯, and p) produced in collisions over a center-of-mass energy range from 2.70 to 200 GeV (per nucleon pair). The modified Tsallis–Pareto-type function (the TP-like function) with average transverse flow velocity is used to describe the contribution of participant or constituent quarks to transverse momentum of considered hadron. The experimental spectra of π∓ and K∓ (or p¯ and p) are fitted by the convolution of two (or three) TP-like functions due to the fact that two (or three) constituent quarks are regarded as two (or three) energy resources in the formation of considered hadron. From the reasonable fits to the spectra, the thermal freeze-out parameters are extracted, and the pseudoentropy is newly defined and extracted. Some parameters quickly change in the energy range of less than 7.7 GeV, and slowly change in the energy range of greater than 7.7 GeV, indicating the variation of collision mechanism at around 7.7 GeV.